2016
DOI: 10.1021/acscatal.6b02702
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Fe/N/C Catalysts in Monolayer Graphene

Abstract: Pyrolyzed Fe/N/C is one of the most promising non-precious-metal catalysts for the oxygen reduction reaction (ORR), which is supposed to boost the commercialization of proton exchange membrane fuel cells (PEMFC). However, the nature of the active sites of Fe/N/C is not clear and has long been debated. The challenges mainly come from highly heterogeneous structures formed during the pyrolysis process as well as no suitable surface probes. To elucidate the active sites, the most effective approach is building we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(60 citation statements)
references
References 38 publications
0
58
0
Order By: Relevance
“…[11] Among the different M-N-C catalysts, Fe-N-Cc atalysts have been studied extensively because of their excellent catalytic activity. [12] Both theoreticalc alculations [13] and experiments [14] have revealed that nitrogen incorporation and Fe-coordinated carbon speciesa re responsible for great improvements in the ORR activity.N evertheless, to date, most Fe-N-C catalysts still suffer from unsatisfactory stability or durability in harsh electrolyte solutionso wing to the instability of iron. [15] More importantly, complicated fabrication processes and expensive chemical reagents also restrict scalablep roduction.…”
Section: Introductionmentioning
confidence: 99%
“…[11] Among the different M-N-C catalysts, Fe-N-Cc atalysts have been studied extensively because of their excellent catalytic activity. [12] Both theoreticalc alculations [13] and experiments [14] have revealed that nitrogen incorporation and Fe-coordinated carbon speciesa re responsible for great improvements in the ORR activity.N evertheless, to date, most Fe-N-C catalysts still suffer from unsatisfactory stability or durability in harsh electrolyte solutionso wing to the instability of iron. [15] More importantly, complicated fabrication processes and expensive chemical reagents also restrict scalablep roduction.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the enhanced ORR performance is mainly related with the M‐N x species and N doping structure. Fe−N 4 and Co−N 4 species of M−N−C structures derived from the metal doping or direct pyrolysis are highly active species for ORR ,,. Furthermore, the ORR performance will be further enhanced when NPs such as Fe, Co, Cu, and Fe 3 C, were encapsulated inside the carbon shell.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
“…FeÀ N 4 and CoÀ N 4 species of MÀ NÀ C structures derived from the metal [207] doping or direct pyrolysis are highly active species for ORR. [106,211,212] Furthermore, the ORR performance will be further enhanced when NPs such as Fe, Co, Cu, and Fe 3 C, were encapsulated inside the carbon shell. The Fe@C NPs can enhance the ORR performance of neighboring FeÀ N x species.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
“…Herein, we synthesized a flower-like V 4 P 6.98 /VO(PO 3 ) 2 catalyst on a nickel foam substrate as an efficient non-noble metal catalyst for electrochemical hydrogen evolution in alkaline electrolyte. Thus, it remains challenging to develop non-noble metal HER catalysts with a high activity for water splitting in alkaline media.Non-noble metal catalysts based on Co, [4][5][6][7][8] Ni, [9][10][11][12][13][14] Fe, [15][16][17] and Mo [5,[18][19][20] have been intensively used as HER catalysts owing to the high abundance of these elements and the their low cost, and high catalytic activities. We report a low-cost and high-efficiency non-noble metal HER catalyst beyond the commonly used transition metals (Ni, Co, Mo, Cu, and Fe), which expands the scope of non-noble-metal phosphide catalysts for water splitting.…”
mentioning
confidence: 99%
“…Non-noble metal catalysts based on Co, [4][5][6][7][8] Ni, [9][10][11][12][13][14] Fe, [15][16][17] and Mo [5,[18][19][20] have been intensively used as HER catalysts owing to the high abundance of these elements and the their low cost, and high catalytic activities. In the past few years, V-based oxides, sulfides, and nitrides show promise for applications in the field of energy conversion and storage, such as supercapacitors and rechargeable batteries for their high-electrochemical performance and earth abundance.…”
mentioning
confidence: 99%